Design of A Hydraulic Power Take-off System for the Wave Energy Device with An Inverse Pendulum - 张大海 李伟 赵海涛 鲍经纬 林勇刚 (China ocean engineering, 2014)
This paper describes a dual-stroke acting hydraulic power take-off （PTO） system employed in the wave energy converter （WEC） with an inverse pendulum. The hydraulic PTO converts slow irregular reciprocating wave motions to relatively smooth, fast rotation of an electrical generator. The design of the hydraulic PTO system and its control are critical to maximize the generated power. A time domain simulation study and the laboratory experiment of the full-scale beach test are presented. The results of the simulation and laboratory experiments including their comparison at full-scale are also presented, which have validated the rationality of the design and the reliability of some key components of the prototype of the WEC with an inverse pendulum with the dual-stroke acting hydraulic PTO system.